An evaluation of arabinogalactan (larafeed® ag) as a nutraceutical growth promoter in starter diets for weanling pigs - J R Bergstrom; J C Woodworth; Jim L Nelssen; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
A nursery study was conducted at the KSU Segregated Early-Weaning Facility to evaluate the effect of dietary arabinogalactan on weanling pig performance. Arabinogalactan is a water-soluble proteoglycan/polysaccharide, most commonly harvested from the bark of the Western Larch (Larix occidentalis) tree, which has demonstrated neutraceutical properties in a limited number of studies with dogs and foals. A total of 288 pigs (initially 14.9 lb) were used in the 35-d experiment. Pigs were blocked by weight and randomly allotted to one of eight dietary treatments fed throughout Phase 1 (d 0 to 14) and Phase 2 (d 14 to 28), followed by a common diet during Phase 3 (d 28 to 35). Four levels of arabinogalactan (0, 0.05, 0.10, and 0.20%) were included in either a negative or positive control diet in a 2 × 4 factorial to form the eight dietary treatments. The negative control diet was a corn-soybean meal based diet without feed-grade antibiotics. The positive control diet was identical to the negative control, but contained a feed-grade antibiotic (Neo-Terramycin with 140 g of neomycin and 140 g of oxytetracycline per ton). The common diet fed during Phase 3 did not contain arabinogalactan, but did contain a feed-grade antibiotic (Neo-Terramycin). From d 0 to 14 (Phase 1), ADG, ADFI, and d 14 weight decreased (linear, P<0.05) with increasing level of arabinogalactan in the diet. Also, pigs fed the positive control diet were heavier (P<0.05) on d 14 than those fed the negative control. During Phase 2 (d 14 to 28) and for the overall treatment period (d 0 to 28), ADG, ADFI, and d 28 weight were improved (P<0.01) for pigs fed the positive control diet compared with pigs fed the negative control. Due to the reduction in ADFI at the highest level (0.20%) of arabinogalactan, ADFI decreased (linear, P<0.05) from d 0 to 28 with increasing arabinogalactan. From d 28 to 35 (Phase 3), when all pigs were fed a common diet, ADG and F/G were poorer for pigs previously fed the positive control. Overall (d 0 to 35), ADG tended to be improved (P<0.07), and ADFI and d 35 weight were improved (P<0.05) for pigs fed the positive control, but F/G was slightly poorer (P<0.05) than for pigs fed the negative control. A reduction (linear, P<0.05) in ADFI was observed for pigs fed increasing arabinogalactan. In conclusion, the addition of arabinogalactan to weanling pig diets did not improve growth performance with the high level (0.20%) resulting in reduced ADFI. However, ADG, ADFI, and d 35 weight were improved by including a feed-grade antibiotic in the Phase 1 and Phase 2 diets.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Antibiotics; Arabinogalactan